Section 19 Conferencing in the Canadian Youth Criminal Justice System - Giberson, Emma (Canadian journal of criminology and criminal justice, 2023)
Under the authority of the Youth Criminal Justice Act (YCJA), Section 19 conferences aim to bring together relevant professionals to discuss diversionary and rehabilitation options for Canadian youth involved in the justice system. However, these options’ use and process has not been examined at the local level where practices may vary from the national vision. To offer insight into their use and processes, the current study used semi-structured qualitative interviews with 40 service providers engaged in Section 19 conferences in New Brunswick, Canada. Although there was perceived value in these conferences (i.e., youth involvement in the process, the sharing of expertise, and collaborative planning across systems), weaknesses in conference processes also were observed (i.e., systemic disorganization, inconsistency in communication and collaboration, concern about effectiveness, and limited resources and support for youth). These findings are discussed in terms of challenges that key stakeholders face in Section 19 conferences that may influence their impact, as well as considerations for areas of improvement in conferencing processes to enhance their value. Overall, Section 19 conferences should be utilized more often, which may be best achieved by clarifying the operational procedures and roles of participants, including elucidating how they can best leverage the roles of stakeholders to service the goals of effective diversion and rehabilitation.